Reactive power based capacitors allocation in distribution network using mathematical remora optimization algorithm considering operation cost and loading conditions - Babanezhad, Manoochehr; Arabi Nowdeh, Saber; Abdelaziz, Almoataz Y.; AboRas, Kareem M.; Kotb, Hossam (Alexandria engineering journal, 2022)
Capacitor allocation is one of the most important topics in distribution network operation. In this paper, reactive power based on capacitors allocation is presented in electrical distribution network using mathematical Remora Optimization Algorithm (ROA) as a powerful optimization method to identify the optimal location and size of the capacitors in the networks. The objective function is defined as minimizing the cost of losses, purchasing and installation costs, as well as the cost of capacitors operation at different loading conditions. Problem optimization variables include the optimal site and size of the capacitors in the network, which is found considering the objective function, operating conditions and reactive size of the capacitors using the ROA. The method based on the ROA is studied on IEEE 33 and 69 buses networks. The simulations are evaluated in different scenarios including capacitors allocation with and without PLNLI as well as in different loading. The simulation results are indicated the capability of the proposed methodology in comparison with previous studies in losses reduction, voltage profile enhancement, reducing annual costs and increasing net saving. The results are also showed that considering PLNLI offers fewer losses, better voltage profiles and of course higher annual cost than the conditions without considering it. In addition, the results clear that reducing the electrical network load level causes reduction of losses cost, voltage fluctuations and also the annual cost of the network. So, optimal implementation of the capacitor allocation based on the ROA in the electrical network can be able to improve the characteristics of the network and also increase the net saving by optimally injecting the reactive power.